Kansas Honor Flight - Wamego High School: service and sacrifice, promise and potential - Hornung, Shawn (Kansas State University, 2015)
The Honor Flight Network is a national non-profit organization based out of Springfield, Ohio, with the mission to “transport our heroes to Washington D.C. to visit and reflect at their memorials.” Kansas Honor Flight – Wamego High School pairs high school students from the local chapter of the National Honor Society with area veterans. This experiential service-learning project provides America’s next generation the opportunity to connect with and learn from America’s “G.I. Generations.” Veterans of World War II, the Korean War, and the Viet Nam War are accompanied by student-guardians who serve as their assistants and guides. The avowed mission is accomplished with students first and foremost providing service for their veteran through the duration of the trip. Yet, the promise of the journey is realized when the student-guardians are able to witness the memorials through the eyes of those who exemplified courage, fortitude, patriotism, service, and sacrifice – flesh and blood representatives of civic virtue. Similarly, the veterans behold the beneficiaries of their sacrifice providing respectful service; virtuous acts voluntary, not obligatory. Different generations of constitutional stakeholders – those who actively preserved the republican experiment, others preparing to be engaged participants therein – experiencing hope for the future as well as gratitude for those who came before. This report includes a narrative of the inaugural mission of Kansas Honor Flight – Wamego High School. Using said narrative as exemplar of following flights, the report chronicles the creation of bridging social capital through implicit reciprocity and the emergence of intergenerational trust-building. The spanning of generations is discussed through the sharing of enduring republican principles. Heroes are democratized as witness is bore by the soldier who lived to tell the tale.
Keywords: Civic educationHonor flight; Service learning; Education, General (0515); Secondary Education (0533); Social Sciences Education (0534)